(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The project focuses on design modification and simulation of a new type of trolley with multifunctional ties. The device was redesigned to have three wheels in a triangular pattern that can be switched into three different working positions to aid in moving of heavy load through a desired vertical height. The project utilized concept generation and selection matrix to generate 30 possible design concepts. These concepts were pruned using concept scoring matrix to three (3) designs. Weighted Scoring Matrix was deployed to screen and rank three best designs. The project design was done using AutoCAD, SolidWorks and Ansys for load/stress analysis of each component. SolidWorks (SimXpress) was deployed for static analysis of the trolley components. Simulation result revealed a weight reduction from 200 kg to 15.3 kg and maximum stress of 7.13 x 108 N/m2 with a 1.5 factor of safety. The trolley design modification shows trolley as a viable option for stair-climbing with lesser physical energy, higher workload capacity and better efficiency.